2009
DOI: 10.1063/1.3222868
|View full text |Cite
|
Sign up to set email alerts
|

Mapping bias-induced phase stability and random fields in relaxor ferroelectrics

Abstract: The spatial variability of polarization reversal behavior in the relaxor 0.9Pb(Mg1/3Nb2/3O3)–0.1PbTiO3 crystal, is revealed on the ∼100 nm scale using switching spectroscopy piezoresponse force microscopy. Quenched fields conjugate to polarization are found, which show mesoscopic (∼100–200 nm) spatial fluctuations around near-zero bias values. The mapping of the stability gap of the bias-induced phase and conjugate random fields is demonstrated. The origin of the observed nanoscale domains and the field-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
(25 reference statements)
2
25
0
Order By: Relevance
“…24 In addition, static PNRs (not reoriented by thermal motion) have been observed in PMN-PT. 32 The configuration of these PNRs seems to be very stable even after the application of an external electric field. It seems that the occurrence of static PNRs is closely related to the presence of chemically ordered regions (CORs).…”
Section: Resultsmentioning
confidence: 99%
“…24 In addition, static PNRs (not reoriented by thermal motion) have been observed in PMN-PT. 32 The configuration of these PNRs seems to be very stable even after the application of an external electric field. It seems that the occurrence of static PNRs is closely related to the presence of chemically ordered regions (CORs).…”
Section: Resultsmentioning
confidence: 99%
“…due to preferential orientation of defects). We observed such a kind of shifts for local loops measured with PFM [24]. Considering the direction and magnitude 2.…”
Section: Introductionmentioning
confidence: 88%
“…Alternatively, truly static PNRs may be responsible for labyrinthine domains. To discriminate between these two possibilities we applied switching spectroscopy PFM [24]. Switching spectroscopy PFM makes it possible to determine the configuration of local quenched electric fields in the material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, labyrinthine domains are in fact frozen spatial fluctuations of polarization caused by the density fluctuations of static PNRs having dipole moment directions up or down. Recent switching spectroscopy PFM experiments 35 showed that static PNRs cannot be switched by an electric field of ϳ10 V ͑i.e., by the bias used in our present work͒. On the other hand, the dynamic PNRs give rise to the observed relaxation.…”
Section: Discussionmentioning
confidence: 99%